Validity, reliability and exploratory factor analysis of the dropout scale in sport centres - Nuviala, A.; Rosario Teva-Villen, M.; Grao-Cruces, A.; Perez-Ordas, R.; Garcia-Fernandez, J.; Nuviala, R. (Journal of Human Sport & Exercise, 2012)
Sport dropout is a complex problem, in which multiple reasons influence. One lacks an instrument of easy application for the sport centres, which there contributes relevant information about dropout motives, at the time that it expires with the properties that any measurement`s instrument must assemble. The aims of this work were to design, to validate and to verify the reliability of a useful instrument as way of evaluation of the motives of the dropout of the organized PA that provide the different sport centres. So, an inventory was made, a statistical analysis of the items was also made, so as an exploratory factor analysis and his validation and his reliability were analyzed. In conclusion, it can be stated that we have a valid and reliable tool to study the phenomenon of dropout in sport centres, which depends on five factors: leisure, enjoyment, satisfaction, practice and economic. The tool has 22 items in total, which makes its application easy.